Decreased Need for Anesthesia during Ultra-Fast Cranial MRI in Young Children: One-Year Summary - Sorge, Ina; Hirsch, Franz Wolfgang; Voit, Dirk; Frahm, Jens; Krause, Matthias; Roth, Christian; Zimmermann, Peter; Gräfe, Daniel (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose Rapid volume coverage sequences based on real-time MRI allow for scanning of the entire brain within a few seconds. Movements of children become almost irrelevant due to the ultra-fast acquisition of 30 ms per slice. The adoption of these sequences in a real-time cranial MRI protocol (RT-cMRI) is expected to reduce the frequency of examinations requiring anesthesia in infants and toddlers. The aim of the study was to quantify the reduction in the number of anesthesia examinations in young children after the implementation of the new RT-cMRI protocol.Materials and Methods All cMRI studies of children up to 6 years in the first 12 months after the establishment of the RT-cMRI 2019/2020 were retrospectively compared to a matched group of the same period in 2017/2018. The frequency of examinations under anesthesia vs. non-sedation examinations was analyzed. In addition, the number of follow-up examinations and the effectiveness of RT-cMRI was determined.Results The launch of RT-cMRI led to a significant decrease in the proportion of cMRI under anesthesia from 92 % to 55 %. Only 2 % of the RT-cMRI failed and required conventional MRI under sedation in the follow-up. The speed and ease of use of RT-cMRI increased the number of follow-up examinations from 1.3 to 1.4 examinations per child.Conclusion This innovative real-time MRI examination allows a drastic reduction in the number of studies under anesthesia for suitable cranial pathologies in children under 6 years. However, cautious selection of indications as well as adjustments to the workflow in the radiological department are required.Key Points: Citation Format
Keywords: sedation; brain; MR imaging